Specificul politicilor publice de ocupare a forţei de muncă în Republica Moldova - Postolachi, Valentina (Calitatea Vieții, 2016)
The rigidity of the labor market becomes an issue of more and more importance considering the shock associated to the economic crises due to the need to increase the adaptability and the speed of response. Thus, public policies aimed at labor market require an orientation towards softening the rigidities determined by the institutional, demographic or mismatching factors between the demand and the supply of the qualified education system. This paper highlights the role of active policies that are aimed at increasing labor market flexibility, stressing the importance and the impact on the operative and effective adaptation towards macroeconomic changes.